2015
DOI: 10.1148/rg.352140095
|View full text |Cite|
|
Sign up to set email alerts
|

Polypoid Lesions of the Gallbladder: Disease Spectrum with Pathologic Correlation

Abstract: Gallbladder polyps are seen on as many as 7% of gallbladder ultrasonographic images. The differential diagnosis for a polypoid gallbladder mass is wide and includes pseudotumors, as well as benign and malignant tumors. Tumefactive sludge may be mistaken for a gallbladder polyp. Pseudotumors include cholesterol polyps, adenomyomatosis, and inflammatory polyps, and they occur in that order of frequency. The most common benign and malignant tumors are adenomas and primary adenocarcinoma, respectively. Polyp size,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 62 publications
1
81
0
3
Order By: Relevance
“…In clinical practice, when tumefactive sludge is incidentally detected at US examination, observation, short-term follow-up with US, or further evaluation with additional imaging modalities usually is performed. This may include contrast material-enhanced US, computed tomography (CT), and magnetic resonance (MR) imaging (1,2). However, no clinical guidelines have been published regarding the treatment of patients with tumefactive sludge seen at US, and to our knowledge, no study exists regarding the rate of malignancy in patients found to have tumefactive sludge at US.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, when tumefactive sludge is incidentally detected at US examination, observation, short-term follow-up with US, or further evaluation with additional imaging modalities usually is performed. This may include contrast material-enhanced US, computed tomography (CT), and magnetic resonance (MR) imaging (1,2). However, no clinical guidelines have been published regarding the treatment of patients with tumefactive sludge seen at US, and to our knowledge, no study exists regarding the rate of malignancy in patients found to have tumefactive sludge at US.…”
Section: Discussionmentioning
confidence: 99%
“…The institutional review board granted approval for the study and waived the requirement for U ltrasonography (US) has a primary role in the imaging of gallbladder diseases including polyps, cholelithiasis, and sludge (1). Although gallbladder polyps and gallstones are relatively common, with a prevalence of 3%-7% and 10%, respectively, at abdominal US, biliary sludge is quite rare in asymptomatic healthy adults (2,3), with a reported prevalence of 0.18%-0.27% (4,5). However, its incidence can be higher in specific clinical situations such as pregnancy (6), total parenteral nutrition (7), rapid weight loss (8), and prolonged fasting in the intensive care unit (9).…”
Section: Subjectsmentioning
confidence: 99%
“…Polypoid gallbladder lesions are commonly seen on US (2.6 % -12.1 % of cholecystectomy specimens) [456]. In primary sclerosing cholangitis and gastrointestinal polyposis syndromes, 60 % of gallbladder polyps are malignant [457].…”
Section: Polypoid Lesionsmentioning
confidence: 99%
“…In primary sclerosing cholangitis and gastrointestinal polyposis syndromes, 60 % of gallbladder polyps are malignant [457]. Malignancy in gallbladder polyps between 6 -10 mm is extremely rare, while polyps > 10 mm are regarded as preinvasive adenomas and papillary neoplasms [456,458]. Adenomas have a wider vascular stalk, thought to be significant, that is best seen on CEUS [456,459].…”
Section: Polypoid Lesionsmentioning
confidence: 99%
See 1 more Smart Citation